SUSTAINABILITY MANAJEMEN MASJID MELALUI PENDAMPINGAN REMAS BAITURRAHMAN BAYEMAN ARJASA SITUBONDO - Hariyanto Hariyanto; Lilit Biati (LP2M Universitas Ibrahimy, 2019)
Setrategis mosque youth as agents in the empowerment of the people need to be equipped with the knowledge and skills needed, for example, the mosque youth activists also need to pursue knowledge of journalism and kewirausahaan.Hal it was important to strengthen propaganda and empowerment umat.Dua that knowledge can be a means of propaganda, as well as increasing HR Teen mosque so that they can be independent. The mosque is an instrument of empowerment of people who have a very strategic role in improving the quality of society. However, it should be backed by good management of the mosque management and integrated. The mosque is used as a community center for the reason that since the time of the Prophet mosque became the center of people's empowerment are not limited only role is the implementation of compulsory worship such as prayer.